ANALISIS GEOMEKANIKA PADA BATUAN DASAR, DI AREA JS-1 RIDGE BAGIAN SELATAN, CEKUNGAN JAWA TIMUR UTARA - Agung Gunawan; Benyamin Sapiie; Bintoro Wibowo (Bulletin of Geology, 2017)
East Java basin is one of production basin in Indonesia. Recently, basement is began evaluated more detail, and also has become one of exploration target in this area. Geomechanics and critically stress fractures analysis are some of methods which is used to evaluate basement potential. These methods are used to evaluate fractures which contribute to fluid flow in basement. Fracture interpretation is done in 2 (two) exploration well, Well-A and Well-B. The result of interpretation show the orientation of natural fracture in both wells is Northeast- Southwest (NE-SW). The orientation of SHmax in Well-B is Northeast Southwest (NE-SW) perpendicular to the breakout fractures. The orientation of Shmin in Well-B is Northwest-Southeast (NW-SE) parallel to breakout fractures. In this research, geomechanics model has only been carried out based on Well-B. The model shows that tectonic regime is strike-slip, the major stress orientation is Northeast-Southwest (NE-SW). The critically stress fracture analysis show that fracture orientation, which is in critical condition, is N 10o-20o E and N 65o E. These fractures are considered contribute to the fluid flow in basement.